Perceived Satisfaction of Students, Teachers, and Parents During the Pandemic Towards Online Teaching - Parinita Ratnaparkhi; Logaıswarı Indıran; Avdhesh Jha; Azamat Maksüdünov (Pamukkale Üniversitesi İşletme Araştırmaları Dergisi, 2022)
With the concepts of online teaching, the study examines online teaching in light of the COVID 19 pandemic effects. Online teaching is a new and different alternative to traditional teaching which was enforced by most governments and education systems in several developing countries due to the pandemic, which in turn raised several questions for teachers, students, and their parents. To this end, the study's primary goal was to learn about the perception of teachers as well as students and parents regarding the satisfaction, merit, and challenges of online teaching. Teachers, students, and parents were all polled in this study. The findings of this study revealed that there is a difference in satisfaction with online teaching, as well as the perceptions of teachers, parents, and students, depending on gender. Along with the merits and challenges of online teaching the current study also examines the perceptions of teachers regarding the difficulties associated with online learning, which in major cases was related to the technology.